Reflexões de Uma Década: Os EUA, o Terrorismo e o 11/09 - Pecequilo, Cristina Soreanu (Meridiano 47 - Journal of Global Studies, 2017)
The aim of the article is to analyze the US and international relations strategic framework ten years after the terrorist attacks of 9/11.